Use of an Amplatzer ASD Occlusion Device for the Closure of an Ascending Aortic Pseudoaneurysm Presenting as Hemoptysis. (11th February 2022) - Kondoleon, Nicholas P.; Kanaan, Christopher; Hansen, Jonathan; Kapadia, Samir R.
Abstract : Aortic pseudoaneurysms can commonly be caused by previous thoracic surgery, trauma, and infection, quickly becoming life-threatening if ruptured. This pathology is typically asymptomatic and incidentally found on imaging; however, few cases have outlined hemoptysis as a presenting symptom for aortic pseudoaneurysms. Traditionally, management of these patients included surgical correction; however, percutaneous approaches have emerged as a safe alternative, helping to reduce the risk of morbidity and mortality associated with surgical correction. This report seeks to describe a case in which hemoptysis was the symptom unveiling the finding of a thoracic ascending aortic pseudoaneurysm and the use of an Amplatzer atrial septal defect (ASD) occlusion device as a viable option to safely resolve the disease process.